Exploring the political economy and social philosophy of Vincent and Elinor Ostrom - Boettke, Peter J.; Herzberg, Bobbi, 1955-; Kogelmann, Brian, 1989- (Economy, polity, and society, 2020)
"The interdisciplinary chapters in this volume explore and engage the work of Vincent and Elinor Ostrom, along with the Bloomington School of political economy more generally"--